Four years of continuous use of soil-biodegradable plastic mulch: impact on soil and groundwater quality - Sintim, Henry Y.; Bandopadhyay, Sreejata; English, Marie E.; Bary, Andy; Liquet y González, José E.; DeBruyn, Jennifer M.; Schaeffer, Sean M.; Miles, Carol A.; Flury, Markus (Geoderma, 2021)
•Environmental impact of soil-biodegradable plastic mulch (SBPM) was assessed.•SBPM increased soil aggregate stability by 6–16% than no mulching.•SBPM increased water infiltration rate by 10–12% than no mulching.•SBPM reduced 4-7 kg ha−1 of nitrate and nitrite leached into groundwater.•The downside, SBPM reduced soil burst CO2-C by 4-54 g kg−1 day−1. There is an increased interest in the use of soil-biodegradable plastic mulch due to limited disposal options for conventional polyethylene mulch. However, information about the impact of continuous use of soil-biodegradable plastic mulch on the environment is limited. Here, we show the effects on soil and groundwater quality from the use of soil-biodegradable plastic mulches for crop production for four consecutive seasons. Two soil-biodegradable plastic mulch products were assessed at two locations (Knoxville, TN and Mount Vernon, WA) having different climates (humid subtropical and cool Mediterranean), with cellulosic-paper mulch, polyethylene mulch, and no-mulch included as control treatments. Soil physical, chemical, and biological properties were first assessed in the spring of 2015 (prior to any field operations), and then a few days after harvest in the fall of 2015, 2016, 2017, and 2018. Water samples were collected in the fall of 2018 from lysimeters installed at 55-cm depth and analyzed for nutrient composition. Compared to the no-mulch treatment, the soil-biodegradable plastic mulches and polyethylene mulch increased the soil aggregate stability (by 6–16%) and water infiltration rate (by 10–12%) by protecting the soil surface from disturbance. Residual nitrate and nitrite under the plastic mulch after harvest were lower than under no-mulch (by 4.1 kg ha−1 to 7.3 kg ha−1) due to increased yield and associated enhanced nutrient uptake. However, plastic mulching, especially the polyethylene mulch, reduced soil microbial activity, measured as burst CO2-C by 6 g kg−1 day−1 to 54 kg−1 day−1, but had no effect on extractable organic carbon concentrations nor specific extracellular enzyme activity rates. Within the four-year period, the soil-biodegradable plastic mulches had overall positive effects on soil and groundwater quality, except for reduced burst microbial respiration, which was more pronounced in Mount Vernon.